التدقيق الشرعي الخارجي وعلاقته بعناصر الحوكمة الشرعية: دراسة تحليلية مقارنة External Shari’ah Audit and Its Relationship to the Elements of Shari’ah Governance: A Comparative Analytical Study - Abdulrahman AlShurafa, Mohamad; Bin Che Abdullah, Ahmad Sufian; Bin Noordin, Kamaruzaman (International Journal of Al-Turath In Islamic Wealth and Finance, 2022)
يعد التدقيق الشرعي الخارجي جزءاً مهماً من منظومة الحوكمة الشرعية في المؤسسات المالية الإسلامية، وقد ظهرت أخيرًا عدة تعليمات ومعايير متعلقة بالتدقيق الشرعي الخارجي، ويهدف هذا البحث للنظر في علاقة التدقيق الشرعي الخارجي بغيره من عناصر الحوكمة الشرعية الأخرى كهيئة الرقابة الشرعية ووظيفة التدقيق الشرعي الداخلي ووظيفة الالتزام الشرعي، ويبين هذا البحث وجود تكامل بين هذه الوظائف في سبيل تحقيق مقصد الالتزام بأحكام الشريعة الإسلامية في عمليات المؤسسات المالية الإسلامية، وقد استخدم البحث المنهج الوصفي في وصف التدقيق الشرعي الخارجي ومنهج المقارنة مع عناصر الحوكمة الشرعية الأخرى المنهج التحليلي في في بيان مدى الحاجة للتدقيق الشرعي الخارجي. Abstract External Shari’ah auditing is considered a significant part of the Shari’ah governance system in Islamic financial institutions; and recently, several instructions and standards with respect to the external Shari’ah auditing have emerged. This research aims to examine the relationship between the external Shari’ah auditing and other elements of Shari’ah governance such as Shari’ah supervisory board, internal Shari’ah auditing, and Shari’ah compliance function. This research evinces the existence of an integration between these functions in order to fulfil the aim of complying with the rulings of Islamic Shari’ah in the operations of Islamic Financial institutions. The research used the descriptive method through describing external Shari’ah auditing; the comparative method by comparing the external Shari’ah auditing to other elements of Shari’ah governance; and the analytical method by clarifying how required is the external Shari’ah auditing.